STRENGTHENING SCIENCE VOCABULARY OF GRADE 10 STUDENTS IN POST-PANDEMIC LEARNING THROUGH PROJECT SCIVOC (Proceedings of the International Conference on Education, 2023)
Pandemic has posed many challenges to society, especially in the education sector. In the conduct of the face-to-face classes after the two years of distance learning, it was evident that the learners had difficulty in understanding Science-related terms. This study focused on a strategy, namely “Project SciVoc: 1 Minute to Define It!”, a game-based activity which aims to help Grade 10 learners understand Science concepts. In every session, students were given a minute to write down all the terms and corresponding definitions they had learned from the previous lessons. Selected Grade 10 students of Plaridel Integrated National High School were the respondents of the study. Mixed methods of quantitative and qualitative research were utilized. For quantitative data, learners’ scores in a long quiz on topics on Plate Tectonics with and without the implementation of the project for the First Quarter of the School Year 2022-2023 was compared. Students had also answered questionnaires using Google Form for their insights of the said activity. The results revealed a significant increase on learners’ score in their long quiz in Plate Tectonics when Project SciVoc was implemented. The results implicate that (1) learners’ vocabulary can be strengthened through game-based activity; (2) learners’ vocabulary can be enhanced through a routine; and (3) learners’ experience and feelings during the activity help them remember and understand concepts. Strengthening learner’s vocabulary is a must for our learners to understand concepts in different learning areas and can be achieved in a collaborative effort of learners, teachers, and community.Keywords: Science vocabulary, strategy, time pressure, post-pandemic
Keywords: Science vocabulary; strategy; time pressure; post-pandemic